Prison Visitation and the Likelihood of Post-Release Employment - Fahmy, Chantal (Crime & delinquency, 2022)
Formerly incarcerated people have a difficult time finding employment upon release. Research has suggested the effectiveness in utilizing one?s social capital and social networks, particularly through family, as a means of securing stable employment post-prison. However, the social connections necessary?maintained via prison visitation?are often weakened due to long-term incarceration and multiple prison stints. Data from the Serious and Violent Offender Reentry Initiative (SVORI) are used to investigate whether individuals were able to find employment within 3?months after release. Results suggest that individuals who have committed serious crimes likely have more strained family relationships; making family members? willingness to vouch for employment on their behalf, less likely. Implications regarding policy and practice for corrections and reentry are discussed.